Evolutionary origin of regulatory regions of retrogenes in Drosophila. - Bai, Y.; Casola, C.; Betrán, E. (BMC Genomics, 2008)
Retrogenes are processed copies of other genes. This duplication mechanism produces a copy of the parental gene that should not contain introns, and usually does not contain cis-regulatory regions. Here, we computationally address the evolutionary origin of promoter and other cis-regulatory regions in retrogenes using a total of 94 Drosophila retroposition events we recently identified. Previous tissue expression data has revealed that a large fraction of these retrogenes are specifically and/or highly expressed in adult testes of Drosophila.In this work, we infer that retrogenes do not generally carry regulatory regions from aberrant upstream or normal transcripts of their parental genes, and that expression patterns of neighboring genes are not consistently shared by retrogenes. Additionally, transposable elements do not appear to substantially provide regulatory regions to retrogenes. Interestingly, we find that there is an excess of retrogenes in male testis neighborhoods that is not explained by insertional biases of the retroelement machinery used for retroposition.We conclude that retrogenes' regulatory regions mostly do not represent a random set of existing regulatory regions. On the contrary, our conclusion is that selection is likely to have played an important role in the persistence of autosomal testis biased retrogenes. Selection in favor of retrogenes inserted in male testis neighborhoods and at the sequence level to produce testis expression is postulated to have occurred.